Analysing and Profiling the Magnetic Field Levels in 330 kV Transmission Stations Switchyard - Abiodun Stephen Moses; Abdullahi Ugbede Usman Ocheni; Mark Ndubuka Nwohu; Onyedi David Oyedum (LPPM Universitas Andalas, 2024)
The investigation of radiated magnetic field intensity in switchyards is of paramount important, so spot measurement procedure was used to detect the levels of magnetic field by placing the detachable sensor of Extech 480826 Triple-Axis metre on ‘constructed stand’ with three reference heights of 1.0, 1.5 and 1.8 m. Instant coordinates of position was simultaneously recorded at each spot during the process of measurements. The analysis revealed locations significant differences of p = 0.027, p = 0.016 and p = 0.023 for the respective reference heights (1.0, 1.5 and 1.8 m). Shiroro and Kainji transmission switchyards mean ELF magnetic field were significant at each height when analysed using least significant differences pairwise comparison. However, non-significant differences between Jebba with Shiroro and also Kainji transmission switchyards were noticed. Further assessment of ELF magnetic field through 2D profiling of height levels in the transmission switchyards display similar drifting path with slight differences and locations with high intensity detected from the plots. The level of instant nonuniformity in mean magnetic field distribution at the switchyards during the duration of the measurements have been revealed by this research and also irregular exposure encountered by workers across height standing at a spot exposed.